Determinants of International Investment Flows: An Empirical Analysis - Bakoeva Gulbakhor (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
This paper investigates the determinants of international investment flows, focusing on foreign direct investment (FDI) and portfolio investment in emerging and developing economies. It uses empirical evidence and theoretical foundations to identify macroeconomic, institutional, and policy factors influencing investment inflows. Based on a comparative analysis of 20 emerging economies from 2010 to 2023, the study highlights the roles of GDP growth, trade openness, exchange rate stability, infrastructure quality, and governance indicators. The findings indicate that stable macroeconomic environments and strong institutions significantly enhance investment attractiveness, while political instability and policy uncertainty reduce capital inflows.